2019
DOI: 10.3389/fpsyg.2019.00536
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Attitudes Toward Traffic Safety Predict Risky Behavior Across Young, Adult, and Older Drivers

Abstract: In the last few decades, several studies have investigated the role of personality traits and attitudes toward traffic safety in predicting driving behaviors in diverse types of drivers across several countries. However, to the best of our knowledge, no studies so far have investigated the possible moderating role played by age in relation to predictors of accident risk. Answering this open question would provide information about the generalizability of the model across different subpopulations and would make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
4
39
0
1
Order By: Relevance
“…In general, it is agreed in the literature that risk behaviors in various social contexts also impact health risks. Studies have shown that personality traits and attitudes towards traffic safety predict dangerous driving behaviors and involvement in accidents [3,7,14,24, 25, 30]. However, this association has not been well investigated among motorcyclists using the psychobiological model of temperament and character.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is agreed in the literature that risk behaviors in various social contexts also impact health risks. Studies have shown that personality traits and attitudes towards traffic safety predict dangerous driving behaviors and involvement in accidents [3,7,14,24, 25, 30]. However, this association has not been well investigated among motorcyclists using the psychobiological model of temperament and character.…”
Section: Discussionmentioning
confidence: 99%
“…Lucidi and colleagues [24] studied drivers´ behaviors considering three different age groups (young: n = 435; adult: n = 412; old: n = 439) in association with personality aspects. The results showed that risk driving was associated with personality traits and anxiety in young and adult drivers, while the search for sensations was associated with risky driving only in young drivers.…”
Section: Introductionmentioning
confidence: 99%
“…At the international level, it is common knowledge that drivers violate traffic rules [11][12][13]. What this report is model-based emphasis that perspectives of the road users determine the associated OHS behavior [11][12][13]; and can be used as predicting factor [14]. Given that knowledge is power, it implies that there is need to empower the people.…”
Section: Implication For Tackling Ohs Issues On the Roadsmentioning
confidence: 99%
“…Crucial developmental transitions, such as physical growth and cognitive, language, and moral development, take place during childhood and adolescence. Over this time, individuals have to solve problems and find opportunities related to schooling and personal life (Alivernini et al 2019;Duprey et al 2018;Girelli et al 2019Girelli et al , 2020Lucidi et al 2019). In doing so, they develop behaviors that will probably last over the entire course of their lives.…”
Section: Introductionmentioning
confidence: 99%